Protestantism and government spendig: A negative relationship? An empirical application to Swiss Cantons - Justina A. V. Fischer; Friedrich Schneider (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Recent empirical growth literature suggests that cultural factors play a decisive role in economic development, while empirical evidence for their impact on government activity remains scant. In this paper, we conjecture based on Weber's Protestant Ethics that 'Protestant values' such as self-reliance and austerity should affect both the size and scope of governments. More specifically, we hypothesize that smaller government budgets should be observable in more Protestant jurisdictions. Using a panel of sub-federal expenditure in 26 Swiss cantons from 1980 to 1998 we find supporting evidence, observing that the share of Protestants in the cantonal residential population exerts a spending dampening impact. Our results suggest that cultural factors should not be omitted from future public finance analyses.
Keywords: A13; H30; H72; Z10; 330; Protestantism; Culture; Government Spending; Public Finance; Protestantismus; Sozialethik; Öffentliche Ausgaben; Teilstaat; Schätzung; Schweiz